Forensic Ornithology: Enlightening People (International Journal of Innovative Research in Computer Science & Technology, 2022)
Ornithology is a division of zoology which  is concerned with the scientific studies of bird.  Ornithologists study the morphology, anatomy, habitat,  behavior, taxonomy, systematics, evolution, eating and  breeding habits of birds. Birds are often the victims of  heinous crimes and aircraft accidents. Forensic ornithology  is a branch of ornithology, which deals with the identification  of the specific bird species from the fragmentary remains at  the site of incident. Forensic Ornithologists use physical  microscopic and DNA bar-coding techniques for comparing  the fragmentary remains and identification. Identification of  the species of the bird helps to understand their true nature,  their habitat, and thus manifest how they can be conserved  and protected from crimes. A bird strike can cause significant  damage to an aircraft and thus to human life. The data on  birds provided by forensic ornithologists can also be used to  stop them from coming to airports and avoid accidents. The  purpose of this review article is to promote the importance of  birds and also the field and scientific techniques of forensic  ornithology and enlighten people about the same. Birds help  to support the climate by going about as hunters, pollinators,  scroungers, seed dispersers, seed hunters, and biological  system engineers. This makes them of decisive and crucial  importance to humans as well as our planet. The right  application of forensic ornithology can lead to safer travels  both of humans and birds.
Keywords: Bird Strike; Forensic OrnithologY; Fragmentary Remains; Scientific Techniques; Zoology